Peran Wali Kelas Dalam Pembentukan Karakter Siswa Kelas 6 di SDIT Al-Fikri Islamic Green School Pekanbaru - Masidayu, Masidayu; Maya Sari, Yolanda; Octavia, Annisa; Islamiati, Tiara; Salsabila, Tia; Eka Putera, Yoanda; Ardiansyah, Ardiansyah; Deprizon, Deprizon (YPI Ulul Albab, 2025)
education can not only be done at home but at school. This character education can be obtained or taught by teachers at school. The aims of this research are: (a To determine the role of the homeroom teacher in developing the character of grade 6 students at SDIT Al Fikri Islamic Greenschool) (b. To determine the role of the homeroom teacher in developing the character values of grade 6 students at SDIT Al Fikri Islamic Greenschool) (c. to find out the problems faced by the class teacher in implementing character development for grade 6 students at SDIT Alfikri). The method used in this research is descriptive qualitative. Which is done by describing a series of events that actually happened to the object that the author is studying. So in this research, informants are needed who can provide clearer information regarding the research problem being carried out. The results of the discussion in this research are that there are six character values implemented by the class teacher at SDIT Al-Fikri in developing student character, namely religious, honest, independent, disciplined, hard working and responsible character values. The value of honesty is reflected in the implementation of religious activities by students and is exemplified by the Class Teacher. The value of honesty is obtained in the habit of students to tell the truth. Independent value is also obtained from the habit of doing assigned tasks yourself or not cheating. Then discipline marks are obtained from the homeroom teacher who sets an example for arriving on time. The value of hard work can also be seen when students remain enthusiastic about learning to achieve their goals and the value of responsibility can be seen from students' efforts to remain trustworthy in the messages given to them.